Rituals in Inclusive Reading Theater: A Design-Based Research Study - Giera, Winnie-Karen (Innovations in Pedagogy and Technology, 2025)
Drama-based learning in inclusive classrooms presents both challenges and opportunities. While not all students are initially motivated to perform, structured drama projects can unlock individual potential by offering various roles and functions. This study explores the intervention “Stop Bullying! A Theater Project”, implemented across 14 settings with over 80 students between 2021 and 2023. Drawing on four cycles of design-based research (DBR), the study analyzes reflective protocols (n = 8) and student feedback (n = 87) to identify how rituals—such as warm-ups, greeting circles, and reflection routines—support inclusive engagement. These practices are examined through the conceptual lens of the Potsdam Inclusive Didactic Teaching Model (PIMODE). While findings demonstrate the pedagogical value of rituals in inclusive theater, the study is limited by its reliance on qualitative data and contextual specificity. Implications are discussed for future inclusive educational design and drama-based literacy instruction. This article contributes meaningfully to the fields of inclusive drama pedagogy and reflective teaching practices by emphasizing the role of structured rituals in literacy development. It offers a practical framework for educators aiming to implement inclusive theatre projects and underscores the ethical dimension of inclusive education. Through its focus on co-constructed routines and emotionally secure learning environments, the study bridges theory and practice in fostering equitable and participatory literacy learning.